Preliminary observations on the effect of light and temperature on the hatching success and rate of Lepidurus arcticus eggs. Issue 4 (4th July 2019) - Pasquali, Vittorio; Calizza, Edoardo; Setini, Andrea; Hazlerigg, David; Christoffersen, Kirsten Seestern
Abstract : Dormancy, which arrests development, is a well-known survival strategy among animals living in the Arctic to overcome harsh periods. It is not clear if the dormant state in notostracans is controlled endogenously (diapause) or exogenously (quiescence). For Lepidurus arcticus, it is unknown how it responds to the photoperiod entrainment, if it has a biological clock and if it has a rhythmic expression of the clock genes. We studied the hatching success of resting eggs at four constant temperatures (5, 10, 15 and 25 °C) and under different illumination regimes [continuous light (LL) and continuous dark (DD)]. It was assumed that light and temperature are both important triggers, with temperature having the most pronounced effect. In our experiment, hatching occurred only at 5 and 10 °C, while we did not observe hatching at 15 and 25 °C. The highest percentage of eggs hatched was at 10 °C in LL (60%); the lowest was at 5 °C in DD (18%). The percentages hatched at 5 °C in LL (24%) and at 10 °C in DD (26%) were similar. Our results indicate that both temperature and light had a significant and interacting effect on hatching in L. arcticus, with temperature being the dominant factor controlling the process. This suggests that changes in temperature affecting the Arctic may significantly impact phenology of this key species in the region. Given that no hatching was observed at 15 °C or above, the persistence of this species may be at risk in areas were arctic lakes are expected to warm to such levels during the summer months.